2013
DOI: 10.1111/ijac.12176
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis and Design of Thermal–Mechanical Stresses in Multilayer Ceramic Capacitors

Abstract: A three‐dimensional finite element model describing the thermal–mechanical stress distribution in multilayer ceramic capacitors (MLCCs) during termination firing, soldering, and bending tests is presented. Numerical results indicate that the thermal residual stresses originating from the soldering process are approximately one‐fifth to half of the magnitude of the flexural stresses at the crack occurrence during the board flex test. The peak tensile stress from numerical simulations correlates with the crack i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…From Table , it can be concluded that the maximum principal stress, which results in cracking of MLCC, at a fixed applied moment increases with the decreasing solder stiffness and solder thickness. Studies of effects of other parameters; for example, inner electrode number, solder wicking height, and lateral margin length, on the stress concentration within MLCCs during bending can be found in a recent publication by Huang et al …”
Section: Discussionmentioning
confidence: 99%
“…From Table , it can be concluded that the maximum principal stress, which results in cracking of MLCC, at a fixed applied moment increases with the decreasing solder stiffness and solder thickness. Studies of effects of other parameters; for example, inner electrode number, solder wicking height, and lateral margin length, on the stress concentration within MLCCs during bending can be found in a recent publication by Huang et al …”
Section: Discussionmentioning
confidence: 99%
“…The slice number is a key influence factor for the performance of single-leg MCTEM. There is an optimal slice number for P, calculated through the formula V 2 /R in , to reach the optimum value, because R in and V for the single-leg MCTEM with electric parallel connection will decrease with increasing slice number 17,21 . Thus, the N n of this n-type single-leg MCTEM has been optimized in this section.…”
Section: Effect Of Slices Number On Module Performancementioning
confidence: 99%
“…During last few decades, the simulation and design of MLESCCs were mainly focused on the mechanical and thermal properties, but there was few work in modeling dielectric breakdown strength, which was the essential property of high‐voltage MLESCCs. Wang et al calculated the concentration of local electric field although a two‐dimensional finite element model by varying some geometric parameters of MLESCCs, and Malay et al discussed the effect of microstructural defects on electric field distribution inside the MLESCC numerically.…”
Section: Introductionmentioning
confidence: 99%